Armament of the Maeotian Horsemen of the 4th Century BC (Based on Materials from the Prikubansky Burial Ground) - Natalya Yu. Limberis; Ivan I. Marchenko (Нижневолжский археологический вестник)
The horsemen, whose graves were discovered in the Prikubansky burial ground, represented the elite of the Maeotian army. Weapons were found in 28 burials. The main types of weapons were iron swords, spearheads, and arrowheads. Swords of the Sindo-Maeotian type were found in 26 burials, and in four burials there were two swords of different lengths. The swords differ in the blade width, the design of the transition space between the guard and the blade, and the shape of the bar-shaped pommel. Spearheads could be found in all the burials. Typically, a set consisted of 4–6 both heavy and light spearheads of various types. One dart tip was found among the spear tips in the three sets. Arrowheads were discovered in twenty burials. Sets of arrows consisted of various numbers of pieces, from a few to several dozens. Mostly, iron three-blade arrowheads were used (415 specimens), bronze (three-blade and triangular) were practically out of use (25 specimens), and bone bullet-shaped ones were represented by isolated finds. The arrows were placed in quivers, which were placed next to or under the sword. In the burials with two swords, there were two quivers. Specific types of weapons are long combat knives (30–42 cm) with bone handles found in seven burials. A set of combat knives could consist of 2–4 pieces. On the grounds of the position in the burial, it can be assumed that the knives were located in a special compartment of the quiver, in a case on the sheath of the sword, or in special wooden sheaths. The equipment of the horsemen included iron axes in the two burials. The dating of the equestrian assemblages is based on a narrow chronology of Greek amphorae from different centers of production, which are present in each burial. The high percentage of horseman complexes among the military burials of the Prikubansky necropolis is probably connected with the location of this group of the Maeotian population near the eastern border of the Asian Bosporus.